MELACAK NEGARA HUKUM IDEAL YANG BERDASARKAN KEADILAN DI INDONESIA - Anshar, Sayid; Ifing, Baso (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract : This study aims to identify the extent to which Indonesia has realized an ideal legal state based on justice. Through an in-depth analysis of regulations, judicial practices, and public perceptions, this study reveals a number of justice deficits that still haunt the Indonesian legal system This study compares the condition of the legal state in Indonesia with universally recognized international standards of justice. Using a human rights framework and the principles of a good rule of law, this study analyzes the extent to which Indonesia's legal system has met these standards. Case studies and comparative analyses are used to identify gaps between legal practices in Indonesia and best practices in other countries. This research highlights the importance of harmonization between national law and international law in order to realize an ideal state of law.Keywords: Ideal Legal State.